α-Hydroxylation of carboxylic acids and amides using bis(trimethylsilyl)peroxide - Manat Pohmakotr (2018)
Bis(trimethylsilyl)peroxide is shown to react with enolate anions derived from carboxylic acids and amides to give the corresponding a-hydroxy derivatives. © 1988, Taylor & Francis Group, LLC. All rights reserved.